Perceived wellness of health sciences students - Henrico, K.; Jordaan, J. (South African Journal of Higher Education, 2026)
In South Africa, the wellness of university students, particularly in health sciences, is influenced by unique socioeconomic, cultural and systemic factors. Although the importance of wellness within higher education has been well documented there seems to still be a dilemma in terms of student wellness during their time at university, especially post-COVID. This study aimed to understand the current wellness landscape by comparing the perceived wellness scores of students from three departments situated within a health sciences faculty of a South African university. To achieve this quantitative comparative methodology was followed. Health sciences students (clinical and non-clinical) completed the self-administered Perceived Wellness Survey (PWS; n=158). This study highlights the disparities in emotional wellness and its implications for holistic development and professional readiness. Overall, female students showed the biggest decline in their PWS and emotional wellness scored the lowest across all factors. Higher Educational Institutions needs to navigate a new wellness landscape post- COVID. Special attention should be given to female and final-year students. As Higher Educational Institutions are implementing wellness initiatives, they need to address the misalignment of emotional wellness seen in this study by adding interventions for each wellness factor, especially emotional wellness.